Rainfall Characteristics and Its Effect on Road Infrastructure Health - Khai Ying, Lim (International Journal of Integrated Engineering, 2019)
Malaysia has a strategic geographical location in which it is protected from most of natural disasters such as earthquakes and typhoons. However, it is affected by flood which is a common occurrence in Malaysia. There is a direct relationship between rainfall and flooding as the increase in rainfall intensity would produce higher runoff. This research is first focused on the four rainfall stations located at the Northeast District of Penang Island, in which its rainfall pattern was determined from 2007 to 2016 and geospatial data analysis has been done by using ArcGIS. The occurrence of flood is found to have great impact on the road infrastructure health. Next, soil commonly used for road foundation (subgrade) in Malaysia was used to investigate the effect of moisture content on subgrade strength, in which the California Bearing Ratio (CBR) test was carried out with increment of moisture content. The findings indicated that the rainfall pattern in Northeast District of Penang Island was affected by the monsoon seasons, in which the Southwest Monsoon brings in more rainfall from April to September. The extreme rainfall during the Southwest Monsoon caused flood to frequently occur in the study area. Total rainfall in the area indicated a decreasing trend in which the total annual rainfall of the latest five years is less than that of the first five years, from 2007 to 2016. However, the intensity of rainfall can be seen on the increasing trend and this is expected to cause greater soil exposure to moisture. The CBR strength of soil is found to be reduced with the increasing moisture content, as the soil bearing capacity is reduced when the soil become saturated. The reduction in subgrade soil’s bearing capacity will affect the performance of the road systems.